Characteristics of Polycystic Ovary Syndrome Polycystic (PCOS) at Soetomo General Hospital, Surabaya - Dhifa Dwi Putra; Dewi Ratna Sari; Jimmy Yanuar Annas; Budi Santoso (Health Notions, 2019)
PCOS is an endocrine disease that occurs in women of reproductive age which is characterized by several clinical manifestations such as hyperandrogen, ovarian dysfunction, and polycystic ovarian features on ultrasound examination. PCOS is an endocrine disease that is closely related to metabolic diseases such as dyslipidemia, diabetes mellitus, and hypertension. Risk factors for this disease are age, environment, genetics, body mass index (BMI), and androgen exposure. The purpose of this study is to determine the profile of PCOS in Soetomo General Hospital, Surabaya. This study used a descriptive retrospective method, using medical record data at the obstetrical clinic at Soetomo General Hospital and fertility clinic at Graha Amerta. Most patients were found in the age range of 25-44 years. Based on the diagnosis of Rotterdam criteria, the phenotype D (Oligo / Amenorrhea and SOPK on USG) was the highest phenotype. People with PCOS who did not have metabolic diseases more than those who have. The highest number of sufferers was found in the category of overweight and obese BMI, which was 35.3% each. Most PCOS sufferers were reproductive age and most have phenotype D. Most sufferers have overweight and obese BMI and do not have metabolic diseases. Keywords: PCOS; infertile; retrospective